2006
DOI: 10.1590/s0104-11692006000300004
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação do sistema de pontuação de intervenções terapêuticas (TISS 28) em unidade de terapia intensiva para avaliação da gravidade do paciente

Abstract: Elias ACGP, Matsuo T, Cardoso LTQ, Grion CMC. Aplicação do sistema de pontuação de intervenções terapêuticas (TISS 28)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
5

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
1
5
0
5
Order By: Relevance
“…When looking at the scores for the two instruments, it can be seen that the TISS‐28 had a lower mean value (19.1 points on admission and 16.8 points on discharge) than has been observed in other studies, with one research finding a mean TISS‐28 score of 21.9 points, another of 23.1 points and a third of 21.4 points . Likewise, higher NEMS scores were shown in this study than for the TISS‐28 for both admission and discharge (22.4 points and 19.0 points, respectively).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…When looking at the scores for the two instruments, it can be seen that the TISS‐28 had a lower mean value (19.1 points on admission and 16.8 points on discharge) than has been observed in other studies, with one research finding a mean TISS‐28 score of 21.9 points, another of 23.1 points and a third of 21.4 points . Likewise, higher NEMS scores were shown in this study than for the TISS‐28 for both admission and discharge (22.4 points and 19.0 points, respectively).…”
Section: Discussionsupporting
confidence: 48%
“…Another study found the cut-off point to be ≥23 points, which indicated a higher probability of death in those patients. 11 Both the admission and discharge had a strong association with the outcome according to cut-off points obtained by ROC curve analysis, with increased odds for the occurrence of death in the high scores. It was possible to verify from the sensitivity analysis that these odds are really magnified on discharge from hospital.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Intervention Score System) que é uma forma numérica, por sistema de escore, de classificação do paciente de acordo com a sua gravidade, levando em consideração a necessidade de intervenções terapêuticas de procedimentos médicos e de enfermagem utilizados (ELIAS et al, 2006). Este método considera que, independentemente do prognóstico, quanto mais terapia o paciente recebe, maior a gravidade da doença e, conseqüentemente, maior o tempo despendido pela enfermagem para este atendimento.…”
Section: Mais Recentemente Também Foi Desenvolvido O Tiss (Therapeuticunclassified
“…O percentual de concordância obedeceu ao preconizado na literatura DAVIS, 1997;WRIGHT;GIOVINAZZO, 2000;RUBIO et al, 2003). (DIAS, 2006;ELIAS et al, 2006; BRITO; GUIRARDELLO, 2011; LEITE; SILVA; PADILHA, 2012).…”
Section: %unclassified